Transfer Pricing in the Global Literature: A Bibliometric Analysis - Ghifari, Farhan Fadil; Dewi, Cynthia Sari; Baresi, Adven Filipi; Hutahuruk, Beryl Ezra; Alam, Hanifah Pagar (West Science Interdisciplinary Studies, 2025)
The objective of this study is to examine the global research landscape related to transfer pricing using a bibliographic approach based on 115 scientific articles indexed in the Scopus database between 2015 and 2025. Utilizing Vosviewer software, analyses of keyword co-occurrence, co-citation, and bibliographic coupling were conducted to identify key topics across countries, influential authors, and patterns of scientific collaboration. The analysis results indicate that transfer pricing, tax issues, and tax avoidance are dominant topics. Emerging subtopics include sustainability, information technology, and business restructuring. While contributions from developing countries remain relatively limited, scientific collaboration is still predominantly led by developed nations. These findings highlight the need to broaden the perspective on transfer pricing research by engaging with the context of developing countries and adopting a more comprehensive, interdisciplinary approach. This study is expected to serve as a foundation for developing research guidelines and transfer pricing policies that can be adapted to a more integrated and global dynamic.